Ուկրաինայի բազմակուսակցական համակարգը. մարտահրավերներ և հեռանկարներ - Վոլոդիմիր Վենհեր (“Center of Perspective Researches and Initiatives” of the Scientific State Committee (Ministryof Education and Science, RA))
Հոդվածում ներկայացվում է Ուկրաինայի կուսակցությունների մասին օրենսդրության զարգացման սահմանադրական և իրավական նախապայմանների և ներկա իրավիճակի ամփոփ նկարագիրը: Դիտարկվում են կուսակցությունների զարգացմանն ուղղված երեք հիմնական մարտահավերներ՝ դրանց գործունեության ու կարգավիճակի վերաբերյալ գործող օրենսդրության մեջ ներկայացված նորույթների տեսանկյունից: Առաջինը կառավարության ‹‹մաքրման›› և ապակոմունիզացիայի վերաբերյալ օրենսդրության ընդունումն ու կիրառումն է: Երկրորդը կուսակցությունների պետական ֆինանսավորման վերականգնումն է, ներառյալ՝ կուսակցությունների կանոնադրական գործունեության ֆինանսավորումը, ինչպես նաև նախընտրական քարոզարշավների ժամանակ իրականացված ծախսերի փոխհատուցումը: Երրորդը կուսակցությունների ֆինանսավորման, դրանց գույքի, եկամուտների և ծախսերի վերահսկման ավելի կոշտ մեխանիզմների կիրառումն է, որը կնպաստի ոչ միայն կուսակցությունների, այլև այլ քաղաքական ինստիտուտների թափանցիկ և բաց գործունեությանը: Այդ մարտահրավերների հաղթահարումը կարող է դառնալ բազմակուսակցական համակարգի ձևավորման և զարգացման հեռանկարային ուղի: The article provides a brief overview of the constitutional and legal conditions and contemporary circumstances for the development of the legislation on political parties in Ukraine. Three main challenges are outlined for the development of political parties in Ukraine in terms of the novelties of country’s current legislation on the status and activities of political parties. Firstly, the adoption and implementation of the legislation regarding the government cleansing and decommunization have considerably influenced the political system of Ukraine and induced the development of extra instruments for the legal regulation of party activities. Another defined challenge is represented by the renewal of the state funding for political parties from the state budget, which accounts for the direct financial support of the statutory activities of political parties as well as reimbursement of their losses during the election campaign. Thirdly, the intro-duction of considerably tougher mechanisms for the control of the political parties’ financing, their property, earnings and expenses should contribute to the rise of transparency and open functioning not only of parties but also of other political institutions in Ukraine. The above-mentioned challenges on condition of their appropriate and logical implementation can become highpotential trends of the development and establishment of multi-party system.
Keywords: Քաղաքականություն